Factors Affecting the Utilization of Active Public Space on the Corridor of Jalan Ijen and Jalan Jakarta - Widiantoro, Wahyu Atiq; Ari, Ismu Rini Dwi; Rukmi, Wara Indira (Graduate School, Universitas Brawijaya, 2024)
Public space is a place where people can carry out their various activities. Urban public space also represents the desire of urban communities to interact with their environment. The development of the form of utilization of public space is dedinitely goes hand in hand with an increase in activity, in terms of type and intensity. The purpose of this study is to find the factors that influence the utilization of active public space on Ijen Street Corridor and Jakarta Street corridors using the Factor Analysis. The results for the factors who affects the utilization of public open space is the experience to interact with another invididual person/doing something together, and the elements that are designing of the site in public space triggering an active attachment feeling to public space in Ijen Street Corridor. While in Jakarta Street Corridor, the results are comfort level of rest by the visitors when doing their activities in the public space, achievement of the criteria of being a good public space, the experience of interacting with another users, and the level of comfort for doing some activities at the public space. Keywords: Factor Analysis, Public Space, Urban Activities